Predicting exchange rates in Asia: New insights on the accuracy of survey forecasts - Frederik Kunze (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This paper evaluates aggregated survey forecasts with forecast horizons of 3, 12, and 24 months for the exchange rates of the Chinese yuan, the Hong Kong dollar, the Japanese yen, and the Singapore dollar vis-à-vis the US dollar using common forecast accuracy measures. Additionally, the rationality of the exchange rate predictions are assessed utilizing tests for unbiasedness and efficiency. All investigated forecasts are irrational in the sense that the predictions are biased. However, these results are inconsistent with an alternative measure of rationality based on methods of applied time series analysis. Investigating the order of integration of the time series and using cointegration analysis, empirical evidence supports the conclusion that the majority of forecasts are rational. Regarding forerunning properties of the predictions, the results are less convincing, with shorter term forecasts for the tightly managed USD/CNY FX regime being one exception. As one important evaluation result, it can be concluded, that the currency regime matters for the quality of exchange rate forecasts.
Keywords: F31; F37; G17; O24; 330; exchange rates; survey forecasts; forecast evaluation; forecast acccuracy; forecast rationality; cointegration; impulse response analysis